Spirulina platensis Suppressed iNOS and Proinflammatory Cytokines in Lipopolysaccharide-Induced BV2 Microglia - Ngu, Ee Ling; Tan, Cheng Yau; Lai, Nicole Jean Yean; Wong, Kah Hui; Lim, Siew Huah; Long, Chiau Ming *; Tan, Kuan Onn *; Phang, Siew Nooi; Yow, Yoon Yen * (MDPI, 2022)
The disease burden of neurodegenerative diseases is on the rise due to the aging population, and neuroinflammation is one of the underlying causes. Spirulina platensis is a well-known superfood with numerous reported bioactivities. However, the effect of S. platensis Universiti Malaya Algae Culture Collection 159 (UMACC 159) (a strain isolated from Israel) on proinflammatory mediators and cytokines remains unknown. In this study, we aimed to determine the anti-neuroinflammatory activity of S. platensis extracts and identify the potential bioactive compounds. S. platensis extracts (hexane, ethyl acetate, ethanol, and aqueous) were screened for phytochemical content and antioxidant activity. Ethanol extract was studied for its effect on proinflammatory mediators and cytokines in lipopolysaccharide (LPS)-induced BV2 microglia. The potential bioactive compounds were identified using liquid chromatography-mass spectrometric (LC-MS) analysis. Ethanol extract had the highest flavonoid content and antioxidant and nitric oxide (NO) inhibitory activity. Ethanol extract completely inhibited the production of NO via the downregulation of inducible NO synthase (iNOS) and significantly reduced the production of tumor necrosis factor (TNF)-α and interleukin (IL)-6. Emmotin A, palmitic amide, and 1-monopalmitin, which might play an important role in cell signaling, have been identified. In conclusion, S. platensis ethanol extract inhibited neuroinflammation through the downregulation of NO, TNF-α and IL-6. This preliminary study provided insight into compound(s) isolation, which could contribute to the development of precision nutrition for disease management.